MODERN ONCO DRUG FOR INTERNAL USE - O. L. Orlova; L. L. Nikolaeva; L. A. Korol; M. V. Dmitrieva; A. P. Polozkova; A. V. Lantsova; I. D. Gulyakin; N. A. Oborotova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
Despite the development of biotherapy, chemotherapy remains one of the main methods of treatment of cancer patients. Currently, there are more than 100 anticancer drug substances, however, every year new drugs enter clinical practice and various therapeutic regimens are tested, expanding the possibilities of therapy and improving the results of treatment. Therefore, the adequate use of modern chemotherapy requires constant updating of information about anticancer drugs and methods of their use. Oral administration of drugs is the most natural and convenient way to introduce drugs into the human body. There are about 75% of orally administered drugs that have the ability to be absorbed in the gastrointestinal tract within 1−3 hours after administration. Oral dosage forms (DF) are most common due to the relative simplicity of their production, convenience of use, accuracy of dosing and high stability. Therefore, pharmaceutical companies often reproduce generics in the form of tablets and capsules for oral administration. However, most active pharmaceutical ingredient (API) are destroyed by the action of the gastrointestinal tract environment, which makes it impossible to use the oral administration. This review of the literature describes the main groups of anticancer drugs that are effective when taken orally. The aim of the study is to compile the information on the main groups of anticancer drugs used internally. Materials and methods. The object of the study was well-known anticancer drugs approved for oral administration. The study was conducted using search information and library databases (eLibrary, PubMed, CyberLeninka, ResearchGate), as well as State Register of Medicinal Remedies. Results and discussion. Analyzing the arsenal of cytotoxic drugs, it should be noted that antitumor substances are characterized by high chemical lability they are photosensitive, heat-labile, hygroscopic and hydrolytically unstable. These properties complicate both obtaining reproducible therapeutic effect when taken orally and technological inprocesses. In addition, anticancer drugs have mutagenic, teratogenic, sensitizing and allergenic effects. Conclusion. Lack of sufficient selectivity of the antitumor effect of cytotoxic drugs and a small breadth of pharmacological action require the use of DF, ensuring control of drug delivery to the body, including dosage accuracy and standard bioavailability. DF plays a very important role in the delivery of drugs to the lesion site. Capsules and coated tablets are necessarily created to avoid high toxicity of anticancer drugs and local tissue reactions when taken orally.